Kondisi Makroekonomi Terhadap Tingkat Pembiayaan Bermasalah Bank Umum Syariah di Indonesia (Periode Januari 2009-Desember 2015 dengan model ECM) - Yudhistira Ardana (Trunojoyo University of Madura, 2017)
The role of banks as financial institutions have never escaped from the credit or financing problems. For Islamic banks, the large amount of funding given to the growing risk of consequences to be borne by the banks concerned. On the other hand, the macroeconomic shocks also have an impact on the financial risk borne by Islamic banking. The purpose of this research is to empirically analyze the effect of macroeconomic conditions (interest rate, GDP, exchange rate, and inflation) on the Non-Performing Ratio (NPF) of Islamic banking in Indonesia in the period January 2009 to December 2015. The data analysis used in this study is Error Correction Model (ECM) of the aggregate data shariah banking in Indonesia.